Protracted low-dose radiation exposure and cataract in a cohort of Chinese industry radiographers. Issue 9 (10th July 2015) - Lian, Yulong; Xiao, Jing; Ji, Xiaoli; Guan, Suzhen; Ge, Hua; Li, Fuye; Ning, Li; Liu, Jiwen
Abstract : Objectives: The aim of this study was to assess the risk of cataract following protracted low doses of radiation exposure among industry radiographers and comparison groups of unexposed workers. Methods: A cohort of 1401 industry radiographers and 1878 unexposed workers in China was followed up for 12 years. The lens doses were based on individual monitoring. Presence of cataract was assessed clinically based on lens photographs using the Lens Opacities Classification System III. Radiation dose–response analyses were performed for cataract incidence by using Poisson regression, adjusting for confounding factors. Results: Industry radiographers were significantly more likely than unexposed workers to develop cortical (HR=2.58, 95% CI 1.36 to 3.82), posterior subcapsular (PSC) cataract (HR=3.57, 95% CI 1.27 to 4.79) and mixed cataract (HR=3.25, 95% CI 1.20 to 6.78), but not nuclear cataract (HR=0.93, 95% CI 0.78 to 1.11). Hypertension, diabetes mellitus, old age at exposure, and high body mass index (>27 km/m 2 ) were significantly associated with increased risk of cortical, PSC and mixed cataracts. However, the risk decreased for regular users of shielded enclosures, lead eyeglasses and lead aprons. No dose–effect relationship was observed for cortical (excess relative risk (ERR)/Sv=0.16; 95% CI −0.04 to 0.36) and PSC cataract (ERR/Sv=0.14; 95% CI −0.90 to 0.76). Conclusions: The results indicated a radiation effect for cortical and PSC cataract at doses less than the annual limit of the International Commission on Radiological Protection (ICRP) guidelines. Regarding current eye risk guidelines, the results challenged the ICRP assumption that cataract is a dose-limiting ocular pathology. Regular use of radiation-protective equipment is therefore strongly recommended for eye safety.